A Safety and the quality of Compost, which is produced from Kashy Company, Duhok, Kurdistan Region - Salem, Salar; Ameen, Hajar; Shareef, Sarwar M. Rasheed (Sulaimani Journal for Pure and Applied Sciences, 2016)
This work presents the safety of municipal solid waste (MSW) compost produced by Kashy Company, and its effects on some soil chemical properties and plant growth. In order to investigate the effects of Kashy Compost on soil properties and growth of chard plant, pot experiment was carried out in an optimum growth condition. This experiment was carried out under greenhouse condition at the Faculty of Agriculture, University of Duhok, using three different treatments consisting of control soil, MSW levels selected for this study were (0) control, (%5W/W) MSW, (%10W/W) MSW, and (%15W/W) MSW. The results obtained in this experiment indicate that application of municipal solid waste improves the plant growth. It was also found that application of municipal solid waste had significantly increased soil pH and EC. The results showed that application of MSW in different rates improved plant growth. Shoots dry and fresh weight were found at a maximum when 5% MSW was applied. Application of MSW gave an increased concentration of heavy metals in plant, especially in 15% MSW treatment.
Keywords: Compost; Chard Growth; Heavy Metals